2019
DOI: 10.1159/000502294
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Patient Health Questionnaire-9 Algorithm for Screening to Detect Major Depression: An Individual Participant Data Meta-Analysis

Abstract: <b><i>Background:</i></b> Screening for major depression with the Patient Health Questionnaire-9 (PHQ-9) can be done using a cutoff or the PHQ-9 diagnostic algorithm. Many primary studies publish results for only one approach, and previous meta-analyses of the algorithm approach included only a subset of primary studies that collected data and could have published results. <b><i>Objective:</i></b> To use an individual participant data meta-analysis to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…Patients with somatoform disorders had the smallest decrease in depressive symptoms ( M = –3.78, SE = 0.27) and patients with eating disorders had the largest decrease in depressive symptoms ( M = –6.19, SE = 0.11). At admission, mean PHQ–9 scores were above the cut-off score of 10 [ 29 ] in all groups. At discharge, mean PHQ–9 scores were below the cut-off score of 10 in all groups except in the patients with trauma-related disorders ( M = 11.6, SE = 0.24).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with somatoform disorders had the smallest decrease in depressive symptoms ( M = –3.78, SE = 0.27) and patients with eating disorders had the largest decrease in depressive symptoms ( M = –6.19, SE = 0.11). At admission, mean PHQ–9 scores were above the cut-off score of 10 [ 29 ] in all groups. At discharge, mean PHQ–9 scores were below the cut-off score of 10 in all groups except in the patients with trauma-related disorders ( M = 11.6, SE = 0.24).…”
Section: Resultsmentioning
confidence: 99%
“…The Chinese version of the PHQ-9 had Cronbach a values of 0.82-0.86 (5,6). In our study, the standard cutoff score of ten and above was used to indicate the occurrence of depressive symptoms (7).…”
Section: Variables and Assessmentmentioning
confidence: 89%
“…The PHQ-9 is one of the most commonly used tools for screening for PSD with high validity and reliability in primary care. One individual patient’s data meta-analysis showed that a cutoff of a score of 10 on the PHQ-9 yielded a maximum diagnostic performance[ 30 ]. Considering the structured interview for DSM as the reference standard for PSD, the sensitivity and specificity of PHQ-9 were 0.82 and 0.97, respectively.…”
Section: Depressive Disorders After Strokementioning
confidence: 99%